GPS Use of the Navigator in the Conduct of Cadastral Work on Agricultural Land - Muzaffarovich, Abdullaev Ashraf; Yarashovich, Sattorov Shahzod; Jaxongir, Kamolov; Abdullo, Akhrorov; Askar, Ochilov (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, ways and recommendations for the use of advanced technologies in the performance of Geodetic and Geo informatics work are presented.